Pensions in a Globalizing World : How Do (N)DC and (N)DB Schemes Fare and Compare on Portability and Taxation? - Genser, Bernd (World Bank, Washington, DC, 2019)
Pensions and broader forms of retirement income do not stop at national borders. As part of globalization, individuals increasingly spend part of their working or retirement life abroad but want to keep or move their acquired rights, accumulated retirement assets, or benefits in payment freely across borders. This raises the issue of the portability and taxation of cross-border pensions in accumulation and disbursement. This paper addresses both portability and taxation issues from the angle of which type of pension scheme defined benefits (DB) or defined contributions (DC) is more aligned with globalization in establishing individual fairness, fiscal fairness, and bureaucratic efficiency. The paper shows that DC schemes tend to dominate DB schemes both at the level of portability and taxation.